A historical prospective study of European stainless steel, mild steel, and shipyard welders. Issue 3 (March 1991) - Simonato, L; Fletcher, A C; Andersen, A; Anderson, K; Becker, N; Chang-Claude, J; Ferro, G; Gérin, M; Gray, C N; Hansen, K S
Abstract : A multicentre cohort of 11, 092 male welders from 135 companies located in nine European countries has been assembled with the aim of investigating the relation of potential cancer risk, lung cancer in particular, with occupational exposure. The observation period and the criteria for inclusion of welders varied from country to country. Follow up was successful for 96.9% of the cohort and observed numbers of deaths (and for some countries incident cancer cases) were compared with expected numbers calculated from national reference rates. Mortality and cancer incidence ratios were analysed by cause category, time since first exposure, duration of employment, and estimated cumulative dose to total fumes, chromium (Cr), Cr VI, and nickel (Ni). Overall a statistically significant excess was reported for mortality from lung cancer (116 observed v 86.81 expected deaths, SMR = 134). When analysed by type of welding an increasing pattern with time since first exposure was present for both mild steel and stainless steel welders, which was more noticeable for the subcohort of predominantly stainless steel welders. No clear relation was apparent between mortality from lung cancer and duration of exposure to or estimated cumulative dose of Ni or Cr. Whereas the patterns of lung cancer mortality in these results suggest that the risk of lung cancer is higher for stainless steel than mild steel welders the different level of risk for these two categories of welding exposure cannot be quantified with precision. The report of five deaths from pleural mesothelioma unrelated to the type of welding draws attention to the risk of exposure to asbestos in welding activities.